Escargot and the Search for Spring - Slater, Dashka; Hanson, Sydney (New York : Farrar Straus Giroux, 2024)
"A cute French snail sets off on a springtime adventure with an adorable bunny in this laugh-out-loud fourth picture book in the bestselling Escargot series--the perfect gift for Easter or all year round."--
Keywords: Snails -- Juvenile fiction; Spring -- Juvenile fiction; Rabbits -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Snails -- Fiction; Spring -- Fiction; Rabbits -- Fiction; Voyages and travels -- Fiction; Picture books